2022
DOI: 10.3390/ijerph19116656
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges and Strategies towards Healthy Eating during COVID-19 Home Confinement Period among Working Adults with BMI ≥ 25 kg/m2 Enrolled in a Weight Loss Program: Qualitative Findings

Abstract: The COVID-19 pandemic has been affecting our lifestyles, such as work, living, and health. In Malaysia, the Restriction of Movement Order (RMO) was first announced in March 2020 to curb the spread of the virus. Since then, many Malaysians have been confined to their own home. This new lifestyle can cause a change of eating habits where healthy eating may be a challenge. Hence, our qualitative study explored the challenges and strategies for healthy eating during the first wave of the COVID-19 home confinement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…Second, though various criteria for diagnosis of PCOS have been proposed by different societies, including National Institutes of Health (NIH) in 1990, Rotterdam criteria in 2003, and Androgen Excess and PCOS Society (AE-PCOS) in 2006 [ 62 , 63 , 64 ], most of the cohort studies enrolled into this meta-analysis adopted Rotterdam criteria, and only one study conducted in 1992 using ultrasound image as diagnostic method was included [ 40 ]. Third, the definitions of BMI were heterogenous in the literatures [ 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Generally, studies conducted in western countries used WHO classification for nutritional status, whereas studies in China partly used WHO classification, partly used lower cutoff for overweightness and obesity (i.e., BMI 24 kg/m 2 and 28 kg/m 2 ) compared to the WHO classification.…”
Section: Discussionmentioning
confidence: 99%
“…Second, though various criteria for diagnosis of PCOS have been proposed by different societies, including National Institutes of Health (NIH) in 1990, Rotterdam criteria in 2003, and Androgen Excess and PCOS Society (AE-PCOS) in 2006 [ 62 , 63 , 64 ], most of the cohort studies enrolled into this meta-analysis adopted Rotterdam criteria, and only one study conducted in 1992 using ultrasound image as diagnostic method was included [ 40 ]. Third, the definitions of BMI were heterogenous in the literatures [ 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Generally, studies conducted in western countries used WHO classification for nutritional status, whereas studies in China partly used WHO classification, partly used lower cutoff for overweightness and obesity (i.e., BMI 24 kg/m 2 and 28 kg/m 2 ) compared to the WHO classification.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies reported that the COVID-19 outbreak exacerbated the obesity epidemic in Malaysia (Tan et al 2022c ; Basir et al 2022 ). Emerging findings are generally in-line with the literature, in which the prevalence of overweight/obesity increased by 4.1% after the pandemic (pre-pandemic = 55.9% versus endemic = 60.0%) (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%